Prophetic Ecological Ethics: A Hadith-Based Analysis of Political Policies and Contemporary Environmental Crises in Indonesia - Rahman Rahman; Ilyas Ilyas; Zulfahmi Alwi; Asrar Mabrur Faza; Djeprin E. Hulawa; M. Husni Thamrin (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2026)
The environmental crisis in Indonesia demonstrates that ecological problems are not solely caused by technical or natural factors, but are also linked to failures in political governance, the dominance of a development paradigm focused on economic growth, and the weak integration of ethical values into the management of natural resources. Various phenomena such as deforestation, agrarian conflicts, ecosystem degradation, weak enforcement of environmental law, and limited public participation in policy-making reflect a gap between the development agenda and the principles of ecological sustainability. This article aims to analyse the relevance of Prophetic Ecological Ethics, derived from the hadith of the Prophet Muhammad (peace be upon him), as an alternative paradigm for both critiquing and reconstructing the direction of environmental policy in Indonesia. This study employs a qualitative method based on a literature review, utilising a normative-textual approach and an analysis of Islamic environmental ethics. Research data was obtained from hadiths concerning the environment, classical Islamic literature, reputable academic articles, and contemporary environmental policy documents. The findings indicate that the Prophet’s hadiths contain fundamental principles such as khalifah (stewardship), amanah (responsibility), mīzān (balance), lā ḍarar wa lā ḍirār (prohibition against causing harm), as well as conservation practices such as hima, which regard nature as a trust to be safeguarded for the benefit of all living beings. These findings demonstrate that Prophetic Ecological Ethics holds theoretical significance as a framework that integrates spiritual, moral, social, and ecological dimensions into environmental governance. Therefore, the integration of prophetic values into public policy, education, and natural resource management has the potential to strengthen ecological justice, sustainable development, and community participation in environmental protection.